2019
DOI: 10.1029/2019wr024816
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Riverine Recharge Impacts on Redox Conditions and Arsenic Release in Groundwater Aquifers Along the Red River, Vietnam

Abstract: Widespread contamination of groundwater with geogenic arsenic is attributed to microbial dissolution of arsenic‐bearing iron (oxyhydr)oxides minerals coupled to the oxidation of organic carbon. The recharge sources to an aquifer can influence groundwater arsenic concentrations by transport of dissolved arsenic or reactive constituents that affect arsenic mobilization. To understand how different recharge sources affect arsenic contamination—in particular through their influence on organic carbon and sulfate cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
3
15
0
Order By: Relevance
“…Therefore, the high resistivities near streams are interpreted as coarse-grained materials associated with natural levee and point bar deposits. Previous research has found increased As near rivers, driven by variation in sediment texture and organic carbon (Yang et al 2014;Nghiem et al 2019).…”
Section: Partial Dependence and Thematic Sensitivity Analysis Illustr...mentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the high resistivities near streams are interpreted as coarse-grained materials associated with natural levee and point bar deposits. Previous research has found increased As near rivers, driven by variation in sediment texture and organic carbon (Yang et al 2014;Nghiem et al 2019).…”
Section: Partial Dependence and Thematic Sensitivity Analysis Illustr...mentioning
confidence: 95%
“…Hydrogeologic characteristics include groundwater age, NGWA.org K.J. Knierim et al Groundwater 60, depth to groundwater, recharge source, and sediment texture (Stute et al 2007;Aziz et al 2008;Sharif et al 2008;Yang et al 2014;McMahon et al 2019;Nghiem et al 2019). The BRT models were developed with direct indicators and surrogates for these characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Groundwater recharge is controlled by a number of factors including precipitation, evapotranspiration, soil type, bedrock geology, climate, vegetation, population among others. Stable isotopes of groundwater provide insight into the seasonal timing and relative efficiency of recharge between seasons (Jasechko et al, 2014(Jasechko et al, , 2017 along with a host of other processes including the degree of evaporation experienced prior to recharge, recharge elevation, surface water-groundwater interaction and connectivity, and paleo-recharge (Siegel and Mandle, 1984;Smith et al, 1992;Squeo et al, 2006;Skrzypek et al, 2015;Follstad Shah et al, 2019;Jasechko, 2019;Nghiem et al, 2019). Thus, understanding spatial patterns in groundwater isotopes greatly aides in characterizing a region's hydrology.…”
Section: Introductionmentioning
confidence: 99%
“…Significant arsenic contamination is also reported in Vietnam. Nghiem et al (2019) reported that 29.2% of randomly sampled household well waters during the regional sampling survey have arsenic concentration below the WHO standards, while the arsenic concentration in 39.3% of the well waters sampled exceeds the Vietnamese standard of 50 µg/L. The authors stated that a high concentration of arsenic was observed in the western (Hanoi) and eastern sides of the Red River.…”
Section: Arsenic In Groundwater Sourcesmentioning
confidence: 99%